The warrior ethos - Pressfield, Steven (Black Irish Entertainment, 2011)
We are all warriors. Each of us struggles every day to define and defend our sense of purpose and integrity, to justify our existence on the planet and to understand, if only within our own hearts, who we are and what we believe in.